Algoritma Denoising & Binarization untuk Perbaikan Kualitas Keterbacaan Citra Takepan Sasak - Lalu Muhammad Samsu; Aswian Editri Sutriandi (Infotek: Jurnal Informatika dan Teknologi, 2018)
Not in the future, Sasak, an ancient manuscript on palm-leaf media from the island of Lombok, experienced quality degradation over time, which worsened the readability of the manuscript. This study explores a combination of denoising and binarization techniques for manuscript image processing with the aim of helping improve future script readability. The experimental results show that the readability level can be improved by different denoising and binarization techniques for different front conditions. The binarization simple thresholding technique and the gaussian adaptive technique are found to generally have the best performance compared to other techniques.DOI : 10.29408/jit.v1i2.902